Associations of time spent on different types of digital media with self-rated general and mental health in Swedish adolescents - Helena Frielingsdorf; Victoria Fomichov; Ingrid Rystedt; Sofia Lindstrand; Laura Korhonen; Hanna Henriksson (Scientific Reports)
Abstract Although previous studies have suggested an association between digital media use and health, detailed knowledge about how different types of digital media impact adolescent health is limited. This cross-sectional population-based study explored the relationship between time spent on various digital media and adolescents’ self-rated general and mental health. The study included 3566 Swedish high school students aged 16–17 years. Associations between time spent on digital media (social media, gaming, watching movies/series/video clips etc. and digital schoolwork) and self-rated health outcomes (general health, self-esteem, symptoms of worry/anxiety and low mood/depression, trust in other people, head/neck/shoulder pain and sleep quality) was assessed. Statistical analyses employed logistic regression models adjusted for covariates (sociodemographic variables and health behaviours). In the adjusted models, spending very high amounts of time (≥ 6 h/day) on any digital media, except schoolwork, was associated with poor self-esteem, symptoms of low mood/depression and poor sleep (ORs 1.35–2.93, p < 0.05). Spending six hours or more on digital media was also associated with worry/anxiety (for social media and gaming), head/neck/shoulder pain (for social media, watching movies/series/video clips and schoolwork), poor general health (for gaming and watching movies/series/video clips) and low trust (for gaming) (ORs 1.39–3.18, p < 0.05). High amounts of time (4–5 h/day) of watching movies/series/video clips was associated with daily symptoms of low mood/depression, neck/shoulder pain, and low trust in other people (ORs 1.46, 1.41, and 1.32, p < 0.05). This study indicates a dose-response relationship between digital media use and adverse health outcomes in adolescents, where adverse associations start to appear after 4–5 h, particularly for watching movies/series/video clips. However, further longitudinal studies, randomized controlled trials and public health interventions focused on healthy and balanced use of digital media are warranted.